ANALISIS DAYA HAMBAT EKSTRAK KUKUS DAN INFUSA LABU KUNING (Cucurbita Moschata) TERHADAP PERTUMBUHAN Escherichia coli - Chylen Setiyo Rini; Fransiska Saputri Leing (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2026)
Diarrhea is a disease caused by pathogenic microorganism infections, one of which is E.coli, which is a serious problem because it can cause death. One alternative treatment utilizes natural ingredients. This experimental study aims to test the effectiveness of pumpkin (C.moschata) extract processed using the steaming and infusion methods on the growth of E. coli bacteria. The yellow squash samples used were sourced from the Larangan market in Sidoarjo, with criteria of freshness and yellow color. The inhibition test was conducted using the Kirby-Bauer method, repeated three times, with extract concentrations of 25%, 50%, 75%, and 100%, a positive control of chloramphenicol, and a negative control of sterile distilled water. The results showed that all extracts exhibited increased antibacterial activity with increasing concentration, with the largest inhibition zone at a concentration of 100%, namely 12.55 mm for steamed pumpkin flesh and 11.61 mm for steamed pumpkin seeds.